Towards Responsible Media: Understanding the Baltic Countries’ Traits Through the Lens of Transparency and Accountability Analysis - Rožukalne, Anda (2024)
This paper explores the idea of a “responsible media environment” through the lens of media organisations’ ownership characteristics. It highlights the significance of “transparency in media ownership” and connects it to the concept of “media market accountability”. As a case example, it looks at the three Baltic countries by assessing how the normative ideal of transparency of media ownership is exercised at the level of media organisations in Estonia, Latvia, and Lithuania. Building on the methodological and theoretical framework of news media monitoring (Trappel & Tomaz, 2022), which highlights the essence of ownership transparency as a valid opportunity to assess the accountability of media organisations, the paper analyses how responsible and open relationships with the audience are fostered in markets defined by specific traditions and structural features, such as their small size. The example of the Baltic countries shows that the small size of the media market leads to a greater reliance on “informal” aspects in relationships regarding media ownership transparency. However, the same element of “informality” contributes to the apparent deficiency and risk identified in the media accountability perspective, which affects expressions of media ownership power, for example, via editorial interventions. As explained, contextual historical factors determine the result, as the rapid transition from socialism to capitalism in these countries in the early 1990s prevented the development of a culture of responsibility among media organisations. Even today, the lack of market accountability instruments in the Baltic media market contributes to the risk that the agenda of media owners primarily determines responsibilities, editorial independence, and media performance.